The Effect of Natural Fiber Percentage on the Tensile Strength of Paper Using ANOVA - Reza Syahputra; Muhammad Sayuti; Fatimah Fatimah; Sri Mutia (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
Paper is generally made of cellulose fibers derived from wood raw materials. Increased demand for production will have an impact on forest exploitation which can lead to environmental stability. Alternative natural fibers containing cellulose fiber are biomass waste such as Galangal Stems (Alpinia Galanga), Pineapple Leaves (Ananas Cosmosus), Banana Stems (Musa Paradisiaca), and others. The use of natural fibers can reduce the exploitation of wood as a raw material for paper. The purpose of this study was to determine the effect of natural fibers consisting of galangal stems, pineapple leaves, banana contains, and waste paper on the tensile strength of paper using ANOVA. The ratio of the percentage of fiber passed is galangal stems 50:10 and 50:40, pineapple leaves 50:10 and 50:40, banana contains 50:10 and 50:40, and waste paper 100% or without comparison. Tensile strength was carried out according to ASTM-D638, then data processing was carried out using the One Way ANOVA method. The results showed that the highest tensile strength value of banana stem paper and waste paper with a ratio of 50:10 was obtained at 7.04262 MPa resulting in the best tensile strength compared to other fibers. Factors that affect the tensile strength are the length of the fiber, and the bonds between the fibers are related to the fiber content. The results of this study concluded that the greater the number of material components in the manufacture of recycled paper, the greater the tensile strength of the report produced.